Secure Implementations for Typed Session Abstractions - Corin, Ricardo; Denielou, Pierre-Malo; Fournet, Cédric; Bhargavan, Karthik; Leifer, James (To appear in the proceedings of the 20th IEEE Computer Security Foundations Symposium (CSF 2007, 2007)
Distributed applications can be structured as parties that exchange messages according to some pre-arranged communication patterns. These sessions (or contracts, or protocols) simplify distributed programming: when coding a role for a given session, each party just has to follow the intended message flow, under the assumption that the other parties are also compliant. In an adversarial setting, remote parties may not be trusted to play their role. Hence, defensive implementations also have to monitor one another, in order to detect any deviation from the assigned roles of a session. This task involves low-level coding below session abstractions, thus giving up most of their benefits. We explore language-based support for sessions. We extend the ML language with session types that express flows of messages between roles, such that well-typed programs always play their roles. We compile session type declarations to cryptographic communication protocols that can shield programs from any low-level attempt by coalitions of remote peers to deviate from their roles. Our main result is that, when reasoning about programs that use our session implementation, one can safely assume that all session peers comply with their roles—without trusting their remote implementations.